Mung bean production as a source of livelihood among farmers in a municipality in the Philippines: Challenges and opportunities - Domingo, Arjhel (Asian Journal of Agriculture and Rural Development, 2023)
This study explored the opportunities and challenges of mung bean production as a source of livelihood among farmers in the municipality of Cuyapo Nueva Ecija, where 223.4 hectares have been devoted to mung bean farming. The study used a descriptive research design and surveyed 214 mung bean farmers from 51 barangays in the municipality. The results of the study revealed that mung bean production provides income to farmers, having a 116.81% return on investment as shown in the cost and return analysis conducted. Mung bean production also provides additional income to local households as many laborers are needed, particularly during the harvesting period. However, mung bean farmers were challenged by the high cost of farm inputs, the low farmgate price of their mung bean harvest, farm destruction caused by stray farm animals, the threat of widespread pest infestation, and the low volume of production. To support the farmers in coping with these challenges, national and local government agencies might provide them with farm input subsidies, cash aid, marketing support, and technical assistance regarding proper crop management.